Review of preclinical data on hyperthermia treatment in lymphomas and its potential for clinical application - Moritz V. Scharr; Frederik Damm; Paul Krahl; Anna Dieper; Paraskevi D. Veltsista; Alexander Hansch; Marcus Beck; Dominik Gerster; Anna-Chiara Giovannelli; Lars Bullinger; Daniel Zips; Pirus Ghadjar (International Journal of Hyperthermia)
Introduction Hyperthermia (HT) at temperatures between 39 °C and 44 °C is utilized as an adjunctive cancer therapy, serving as potent radio- and chemosensitizer. Its effectiveness in treating solid malignancies has been well established. This raises the question of whether HT can also benefit patients with nonsolid tumors, such as lymphomas.Objective To provide an overview of the current literature on research involving the use of HT in the treatment of lymphomas.Material and Methods This systematic literature review was conducted following the PRISMA guidelines. For this purpose, a MeSH-term-defined literature search on MEDLINE (Pubmed) and Embase (Ovid) was conducted from June 25 to June 28, 2024. Included were in vitro studies on lymphoma cell lines and preclinical studies on animal models with lymphoma that were both treated with HT as monotherapy or HT in combination with another treatment, and studies on patients with lymphoma. Excluded were studies that used thermal ablation and hyperthermic perfusions.Results Thirty-nine studies were included, predominantly in vitro studies (n = 32) or studies on animal models (n = 5). The in vitro studies utilized HT either as monotherapy (n = 6), with substances that enhance HT efficacy (n = 18) or as a sensitizer for other treatments (n = 8). Additionally, two clinical case reports on the treatment of lymphoma patients were included.Conclusions In vitro results suggest that HT can have anticancer effects on lymphoma cells and may enhance existing treatments. These findings are supported by in vivo studies and case reports. However, additional clinical data are needed before translation into the clinic can be implemented.